Rfc4 Interacts with Rpa1 and Is Required for Both DNA Replication and DNA Damage Checkpoints in Saccharomyces cerevisiae - Kim, Hee-Sook (American Society for Microbiology, 2001)
The large subunit of replication protein A (Rpa1) consists of three single-stranded DNA binding domains and an N-terminal domain (Rpa1N) of unknown function. To determine the essential role of this domain we searched for mutations that require wild-type Rpa1N for viability in yeast. A mutation in RFC4, encoding a small subunit of replication factor C (RFC), was found to display allele-specific interactions with mutations in the gene encoding Rpa1 (RFA1). Mutations that map to Rpa1N and confer sensitivity to the DNA synthesis inhibitor hydroxyurea, such as rfa1-t11, are lethal in combination with rfc4-2. The rfc4-2 mutant itself is sensitive to hydroxyurea, and like rfc2 and rfc5 strains, it exhibits defects in the DNA replication block and intra-S checkpoints. RFC4 and the DNA damage checkpoint gene RAD24 were found to be epistatic with respect to DNA damage sensitivity. We show that the rfc4-2 mutant is defective in the G(1)/S DNA damage checkpoint response and that both the rfc4-2 and rfa1-t11 strains are defective in the G(2)/M DNA damage checkpoint. Thus, in addition to its essential role as part of the clamp loader in DNA replication, Rfc4 plays a role as a sensor in multiple DNA checkpoint pathways. Our results suggest that a physical interaction between Rfc4 and Rpa1N is required for both roles.